Young people’s use of new media: learning through participation in communities of practice - Nurzali Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study explored young people’s use of new media and the learning that they experience through participation in shared online practices such as web browsing, using social media and gaming. The findings of this study revealed that the research participants have rich new media access and they engage in a variety of digital practices at an extended period of time at home. Their use of new media often involves other associates. The research participants’ mutual engagement with other associates based on the shared digital practices that they participate in, the joint enterprise and shared repertoire indicate their belonging to communities of practice (COPs). Learning occurs as result of the research participants’ active participation in shared new media practices with their associates. This kind of learning is social, and it takes place with or without them noticing it.